Biosurfactants from marine thermophilic bacilli for mitigating soil dehydration and preventing plant diseases - V. Zammuto; A. Macrì; M. T. Caccamo; S. Magazù; E. Conti; D. Leone; A. Spanò; C. Gugliandolo (International Journal of Environmental Science and Technology, 2026)

Unveiling “Mid-Pliocene Warm Period” dynamics through multiproxy stratigraphic analysis: The Valdelsa Basin in Northern Apennines – Italy as a key archive - L. Milaneschi; G. Cornamusini; P. Conti; I. Martini; J. Maffei; F. Cifelli; M. Mattei; S. Da Prato; M.C. Alçiçek; L.M. Foresi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Molecular detection of Escherichia coli virulence factors in swine isolates: A systematic review and meta-analysis - Elisa De Conti; Rodrigo C. Paiva; Brad Kuennen; Giovani Trevisan; Daniel C.L. Linhares; Annette M. O’Connor; Marcelo N. Almeida (Veterinary Microbiology, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Biopsychosocial frailty and the incident risk of cardio- and cerebrovascular diseases: an 8-year follow-up of the italian longitudinal study on aging - Vincenzo Solfrizzi; Emanuele Scafato; Madia Lozupone; Carlo Custodero; Vittorio Dibello; Donato Cirrottola; Claudio Pace; Marika Rizzato; Andrea Schilardi; Claudia Gandin; Silvia Ghirini; Rodolfo Sardone; et al. (GeroScience, 2026)

Associations between per- and polyfluoroalkyl substances and metabolic dysfunction-associated steatotic liver disease in adolescents and young adults: modifying roles of age, lifestyle factors, and PNPLA3 genotype - Shiwen Li; Jiawen Carmen Chen; Elizabeth Costello; Douglas I. Walker; Jesse A. Goodrich; Lily Dara; Lucy Golden-Mason; Ana C. Maretti-Mira; Scott M. Bartell; Veronica M. Vieira; Tanya L. Alderete; Michael I. Goran; et al. (Environmental Research, 2026)

Corrigendum to “Edaphobase 2.0: Advanced international data warehouse for collating and using soil biodiversity datasets” [Applied Soil Ecology 204 (2024) 105710] - D.J. Russell; E. Naudts; N.A. Soudzilovskaia; M.J.I. Briones; M. Çakır; E. Conti; J. Cortet; C. Fiera; D. Hackenberger Kutuzovic; M. Hedde; K. Hohberg; D. Indjic; et al. (Applied Soil Ecology, 2026)

Extracellular vesicle-associated miR-222-3P and miR-186-5P as hypoxic markers in canine osteosarcoma: An in vitro study - R. De Maria; L. Maniscalco; M. Poncina; S. Divari; L. Parisi; S. Sonia; L. Cesar Conti; E. Mazzone; L. Aresu (Journal of Comparative Pathology, 2025)

Immunohistochemical profiling of B7-H3 expression in canine solid and liquid neoplasms - L. Cesar Conti; S. Capellero; S. Divari; L. Maniscalco; E. Mazzone; M. Olimpo; L. Aresu; R. De Maria (Journal of Comparative Pathology, 2025)

Short-chain per- and polyfluoroalkyl substances associate with elevated alanine aminotransferase: Cross-sectional analysis results from the STRIVE cohort - Bojung Seo; Hongxu Wang; Rachel Maguire; Yukun Liu; Beatrice Smith; Kristin Haller; Marjorie Riggan; David V. Conti; Heinz-Josef Lenz; Kara Wegermann; Antonio Planchart; Giorgio Roccaro; et al. (Environmental Research, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Examining disparities in PFAS plasma concentrations: Impact of drinking water contamination, food access, proximity to industrial facilities and superfund sites - Shiwen Li; Jesse A. Goodrich; Elizabeth Costello; Douglas I. Walker; Carlos Cardenas-Iniguez; Jiawen Carmen Chen; Tanya L. Alderete; Damaskini Valvi; Sarah Rock; Sandrah P. Eckel; Rob McConnell; Frank D. Gilliland; et al. (Environmental Research, 2025)

Edaphobase 2.0: Advanced international data warehouse for collating and using soil biodiversity datasets - D.J. Russell; E. Naudts; N.A. Soudzilovskaia; M.J.I. Briones; M. Çakır; E. Conti; J. Cortet; C. Fiera; D. Hackenberger Kutuzovic; M. Hedde; K. Hohberg; D. Indjic; et al. (Applied Soil Ecology, 2024)

Natural-based solutions to mitigate dietary microplastics side effects in fish - N. Cattaneo; M. Zarantoniello; F. Conti; A. Tavano; A. Frontini; I. Sener; G. Cardinaletti; I. Olivotto (Chemosphere, 2024)

Exposure to per- and polyfluoroalkyl substances and alterations in plasma microRNA profiles in children - Yijie Li; Brittney O. Baumert; Nikos Stratakis; Jesse A. Goodrich; Haotian Wu; Shelley H. Liu; Hongxu Wang; Emily Beglarian; Scott M. Bartell; Sandrah Proctor Eckel; Douglas Walker; Damaskini Valvi; et al. (Environmental Research, 2024)

P13-17 Assessment of the efficiency of the literature search of the ten key characteristics of carcinogens in the IARC Monographs evaluation process - C. Facchin; A. De Conti; L. Benbrahim-Tallaa; S. Chittiboyina; S. Ruiz; M. Schubauer-Berigan; F. Madia (Toxicology Letters, 2024)

Expression of miRNA from spent pre-implantation embryos culture media - Claudia Omes; Alice Conti; Laura Benedetti; Veronica Tomasoni; Davide De Marchi; Rossella E. Nappi; M. Gabriella Cusella De Angelis; Gabriele Ceccarelli (Reproductive Biology, 2024)

The last cave lion of the late Upper Palaeolithic: The engraved feline of Grotta Romanelli (southern Italy) - D. Sigari; C. Bourdier; C. Conti; J. Conti; L. Forti; M. García-Diez; G. Lai; I. Mazzini; P. Pieruccini; R. Sardella (Quaternary Science Reviews, 2024)

Correction to: A1R–A2AR heteromers coupled to Gs and Gi/0 proteins modulate GABA transport into astrocytes - Sofia Cristóvão-Ferreira; Gemma Navarro; Marc Brugarolas; Kamil Pérez-Capote; Sandra H. Vaz; Giorgia Fattorini; Fiorenzo Conti; Carmen Lluis; Joaquim A. Ribeiro; Peter J. McCormick; Vicent Casadó; Rafael Franco; et al. (Purinergic Signalling, 2024)

Biogeography of orchids and their pollination syndromes in small Mediterranean islands - M. Lussu; P. Zannini; R. Testolin; D. Dolci; M. Conti; S. Martellos; A. Chiarucci (Journal of Biogeography, 2024)
Aims Despite the research on orchid in insular conditions, few studies are focused on the spatial distribution of their reproductive syndromes across complex insular systems. By using island species–area relationships (ISAR), we explore orchid biogeography in the Central Western‐Mediterranean islands. In this study, we aim to investigate variation in ISARs using orchid pollination mechanisms as proxies to establish permanent populations explaining how the c and z parameters of ISARs vary among island types and pollination strategies and defining the most influential factors in shaping orchids' distribution. Location Mediterranean Basin. Taxon Orchidaceae. Methods Checklist of native orchids was obtained for 112 islands of Central‐Western Mediterranean Basin. The Arrhenius power function () was used to fit ISARs for the total number of orchids as well as for functional groups defined by the pollination strategies, across different island types. We used GLM to investigate the relation between pollination syndromes with area and isolation as well as elevation, island origin, taxa richness of the source area and habitat diversity. Results We found that ISARs differ between continental and volcanic islands depending on isolation. The z ‐value was found to be higher for more specialized strategies while the c ‐value increases from autogamy to allogamy, supporting the role of these two parameters in understanding distributional dynamics. Distance from the mainland is a negative predictor for all the strategies except when deception is decoupled; island area is a positive predictor only for allogamic, deceptive and food deceptive strategies, while habitat diversity is a positive predictor for allogamic, rewarding and deceptive strategies. Main Conclusions Pollination syndromes contribute in explaining the distribution of orchids in insular conditions. Furthermore, we identified differences in ISARs across pollination syndromes in which the intercept increases when the pollination shifts from a generalist to a more specialized one.

A second update to the checklist of the vascular flora native to Italy - F. Bartolucci; L. Peruzzi; G. Galasso; A. Alessandrini; N. M. G. Ardenghi; G. Bacchetta; E. Banfi; G. Barberis; L. Bernardo; D. Bouvet; M. Bovio; G. Calvia; et al. (Plant Biosystems, 2024)

A second update to the checklist of the vascular flora alien to Italy - G. Galasso; F. Conti; L. Peruzzi; A. Alessandrini; N. M. G. Ardenghi; G. Bacchetta; E. Banfi; G. Barberis; L. Bernardo; D. Bouvet; M. Bovio; M. Castello; et al. (Plant Biosystems, 2024)

Breast density in NF1 women: a retrospective study - R. De Santis; G. Cagnoli; B. Rinaldi; D. Consonni; Beatrice Conti; M. Eoli; A. Liguori; M. Cosentino; G. Carrafiello; O. Garrone; M. Giroda; C. Cesaretti; et al. (Familial Cancer, 2024)
Neurofibromatosis type 1 (NF1) is an autosomal dominant condition caused by neurofibromin haploinsufficiency due to pathogenic variants in the NF1 gene. Tumor predisposition has long been associated with NF1, and an increased breast cancer (BC) incidence and reduced survival have been reported in recent years for women with NF1. As breast density is another known independent risk factor for BC, this study aims to evaluate the variability of breast density in patients with NF1 compared to the general population. Mammograms from 98 NF1 women affected by NF1, and enrolled onto our monocentric BC screening program, were compared with those from 300 healthy subjects to verify differences in breast density. Mammograms were independently reviewed and scored by a radiologist and using a Computer-Aided Detection (CAD) software. The comparison of breast density between NF1 patients and controls was performed through Chi-squared test and with multivariable ordinal logistic models adjusted for age, body mass index (BMI), number of pregnancies, and menopausal status.breast density was influenced by BMI and menopausal status in both NF1 patients and healthy subjects. No difference in breast density was observed between NF1 patients and the healthy female population, even after considering the potential confounding factors.Although NF1 and a highly fibroglandular breast are known risk factors of BC, in this study, NF1 patients were shown to have comparable breast density to healthy subjects. The presence of pathogenic variants in the NF1 gene does not influence the breast density value.

The transition from normal marine to evaporitic conditions recorded in a cold seep environment: The Messinian succession of Northern Italy - S. Conti; C. Argentino; M. Bojanowski; C. Fioroni; S. Giunti; B. Kremer; D. Fontana (Marine and Petroleum Geology, 2024)

New olive-pomace fertilizer tested with a 2-tiers approach: Biomarkers on Eisenia fetida, physiochemical effects on Solanum lycopersicum and Olea europaea - S. Parri; T. Campani; V. Conti; G. Cai; M. Romi; S. Casini; R. Zari; F. Caldini; L. Marsili (Journal of Environmental Management, 2024)

Numerical modeling of the influence of reservoir management on the algal blooms of San Roque - J. Muchiut; M. I. Rodríguez; A. L. Ruibal Conti; M. Ruiz; A. Rodríguez (International Journal of Environmental Science and Technology, 2024)

Are hospital wastewater treatment plants a source of new resistant bacterial strains? - Gisele Canan-Rochenbach; Marco A.B. Barreiros; André O.S. Lima; Aline Dal Conti-Lampert; Rafael Ariente-Neto; Wendell Pimentel-Almeida; Rosane Laçoli; Rogério Corrêa; Claudemir M. Radetski; Sylvie Cotelle (Environmental Science and Pollution Research, 2023)

P03-14: Cancer Hazard Identification in the IARC Monographs: Recent evaluations for which cancer in experimental animals and toxicological evidence was influential - L. Benbrahim-Tallaa; F. El Ghissassi; A. De Conti; M. Schubauer-Berigan; F. Madia (Toxicology Letters, 2023)

OS02-04: Advancing the evaluation of mechanistic evidence in cancer hazard identification: update on the IARC key characteristic (KCs) of carcinogens framework - F. Madia; A. De Conti; F. El Ghissassi; L. Benbrahim-Tallaa; M. Schubauer-Berigan (Toxicology Letters, 2023)

Tumor and peritumoral adipose tissue crosstalk: De-differentiated adipocytes influence spread of colon carcinoma cells - G. Conti; L. Calderan; L.A. Quintero Sierra; A. Conti; R. Ossanna; F. Boschi; P. Marzola; F. Ferrarini; M. Governa; P.M.-J. Lievens; A. Sbarbati (Tissue and Cell, 2023)

Different molecular changes underlie the same phenotypic transition: Origins and consequences of independent shifts to homostyly within species - Emiliano Mora‐Carrera; Rebecca L. Stubbs; Barbara Keller; Étienne Léveillé‐Bourret; Jurriaan M. de Vos; Peter Szövényi; Elena Conti (Molecular Ecology, 2023)
The repeated transition from outcrossing to selfing is a key topic in evolutionary biology. However, the molecular basis of such shifts has been rarely examined due to lack of knowledge of the genes controlling these transitions. A classic example of mating system transition is the repeated shift from heterostyly to homostyly. Occurring in 28 angiosperm families, heterostyly is characterized by the reciprocal position of male and female sexual organs in two (or three) distinct, usually self‐incompatible floral morphs. Conversely, homostyly is characterized by a single, self‐compatible floral morph with reduced separation of male and female organs, facilitating selfing. Here, we investigate the origins of homostyly in Primula vulgaris and its microevolutionary consequences by integrating surveys of the frequency of homostyles in natural populations, DNA sequence analyses of the gene controlling the position of female sexual organs ( CYPᵀ ), and microsatellite genotyping of both progeny arrays and natural populations characterized by varying frequencies of homostyles. As expected, we found that homostyles displace short‐styled individuals, but long‐style morphs are maintained at low frequencies within populations. We also demonstrated that homostyles repeatedly evolved from short‐styled individuals in association with different types of loss‐of‐function mutations in CYPᵀ . Additionally, homostyly triggers a shift to selfing, promoting increased inbreeding within and genetic differentiation among populations. Our results elucidate the causes and consequences of repeated transitions to homostyly within species, and the putative mechanisms precluding its fixation in P. vulgaris . This study represents a benchmark for future analyses of losses of heterostyly in other angiosperms.

Metronidazole Degradation by Physico-chemical and Advanced Oxidative Processes: Influence of pH and nTiO2-Functionalized Macroporous Support - Eric Sanches-Simões; Renan C. Testolin; Felipe M. Müller; Otto M. S. Gerlach; Wendell Pimentel-Almeida; Aline Dal Conti-Lampert; Albertina X. R. Corrêa; Gizelle I. Almerindo; Sergio Y. Gómez González; Claudemir M. Radetski (Water, Air, & Soil Pollution, 2022)

Evidence for trophic niche partitioning among three temperate gorgonian octocorals - Inga E. Conti-Jerpe; Joseph R. Pawlik; Christopher M. Finelli (Coral Reefs, 2022)
Trophic niche theory predicts that species in competition for a limiting resource will evolve adaptations allowing them to consume alternative resources and occupy new niche space. Trophic niche partitioning is often identified by differences in the morphology of feeding structures across species; however, these differences may not always be readily observable. Due to their constrained polyp morphology, octocorals are often viewed a single functional group that contributes to benthic-pelagic coupling by feeding opportunistically on available particles. To test the hypothesis that sympatric gorgonians share the same trophic niche, feeding selectivity of three gorgonian species ( Leptogorgia virgulata, Muricea pendula, and Thesea nivea) was compared using a combination of flume experiments and stable isotope analysis. The tentacle length and polyp surface area of L. virgulata and T. nivea were also measured and compared. In flume experiments, clearance of rotifers (“typical” zooplankton) and a mixture of cultured phytoplankton indicated that L. virgulata and T. nivea fed on zooplankton and not phytoplankton. Stable isotope values for all three species are consistent with distinct trophic niches, with M. pendula occupying a lower trophic level. Thesea nivea was found to have significantly larger polyp surface area and tentacle length; however, this did not appear to explain observed trophic differences. The results of this study provide evidence for niche partitioning, but future work is required to better understand the mechanism behind this divergence.

El Niño teleconnection to the Euro-Mediterranean late-winter: the role of extratropical Pacific modulation - Marianna Benassi; Giovanni Conti; Silvio Gualdi; Paolo Ruggieri; Stefano Materia; Javier García-Serrano; Froila M. Palmeiro; Lauriane Batté; Constantin Ardilouze (Climate Dynamics, 2022)
El Niño Southern Oscillation (ENSO) represents the major driver of interannual climate variability at global scale. Observational and model-based studies have fostered a long-standing debate on the shape and intensity of the ENSO influence over the Euro-Mediterranean sector. Indeed, the detection of this signal is strongly affected by the large internal variability that characterizes the atmospheric circulation in the North Atlantic–European (NAE) region. This study explores if and how the low-frequency variability of North Pacific sea surface temperature (SST) may impact the El Niño-NAE teleconnection in late winter, which consists of a dipolar pattern between middle and high latitudes. A set of idealized atmosphere-only experiments, prescribing different phases of the anomalous SST linked to the Pacific Decadal Oscillation (PDO) superimposed onto an El Niño-like forcing in the tropical Pacific, has been performed in a multi-model framework, in order to assess the potential modulation of the positive ENSO signal. The modelling results suggest, in agreement with observational estimates, that the PDO negative phase (PDO − ) may enhance the amplitude of the El Niño-NAE teleconnection, while the dynamics involved appear to be unaltered. On the other hand, the modulating role of the PDO positive phase (PDO + ) is not reliable across models. This finding is consistent with the atmospheric response to the PDO itself, which is robust and statistically significant only for PDO − . Its modulation seems to rely on the enhanced meridional SST gradient and the related turbulent heat-flux released along the Kuroshio–Oyashio extension. PDO − weakens the North Pacific jet, whereby favoring more poleward propagation of wave activity, strengthening the El Niño-forced Rossby wave-train. These results imply that there might be conditional predictability for the interannual Euro-Mediterranean climate variability depending on the background state.

Probabilistic Damage Stability for Passenger Ships—The p-Factor Illusion and Reality - Dracos Vassalos; M. P. Mujeeb-Ahmed; Donald Paterson; Francesco Mauro; Fabien Conti (Journal of Marine Science and Engineering, 2022)
The paper complements an earlier publication by the authors addressing the probability of survival in the IMO framework for damage stability assessment, the s-factor. The focus here is on the probability of occurrence of a certain damage scenario (breach), conditional on its dimensions and location (centre and port or starboard side), the p-factor. Pertinent assumptions and limitations are explained, following its evolution for specific application to passenger ships. Attempts to provide analytical descriptions of the damage breach distributions as tetrahedra shapes positioned along the ship length whilst accounting for changes in ship geometry, structural arrangements, and subdivision for consumption by the wider profession has led to misconceptions and misunderstandings of what exactly the p-factor is in the context of probabilistic damage stability calculations. This is evidenced by the fact that the same original damage breach distributions, derived in Project HARDER, based on largely cargo ships with the age spread over the last three decades of the previous century, are still being used today for all ship types, including modern passenger ships. Filling this gap, a new database for passenger ships developed in the EC-funded Project FLARE, is briefly presented, leading to new damage breach distributions specifically for passenger ships. It is believed that this paper will throw considerable light in enhancing understanding on the p-factor, which has been cluttered with unnecessary complexity from the outset.

Correction to: Can Pharmacokinetic Studies Assess the Pulmonary Fate of Dry Powder Inhaler Formulations of Fluticasone Propionate? - Günther Hochhaus; Mong-Jen Chen; Abhinav Kurumaddali; Uta Schilling; Yuanyuan Jiao; Stefanie K. Drescher; Elham Amini; Simon M. Berger; Bhargava Kandala; Christine Tabulov; Jie Shao; Brandon Seay; et al. (The AAPS Journal, 2022)

Can Pharmacokinetic Studies Assess the Pulmonary Fate of Dry Powder Inhaler Formulations of Fluticasone Propionate? - Günther Hochhaus; Mong-Jen Chen; Abhinav Kurumaddali; Uta Schilling; Yuanyuan Jiao; Stefanie K. Drescher; Elham Amini; Simon M. Berger; Bhargava Kandala; Christine Tabulov; Jie Shao; Brandon Seay; et al. (The AAPS Journal, 2021)

Effects of tetracycline on entomopathogenic nematodes and their bacterial symbionts - M. Clausi; D. Leone; A. Strano; A. Lizio; G. Rappazzo; C. Mulder; E. Conti (Ecotoxicology, 2021)

Genetic basis of susceptibility to low‐dose paraquat and variation between the sexes in Drosophila melanogaster - Pamela C. Lovejoy; Kate E. Foley; Melissa M. Conti; Samantha M. Meadows; Christopher Bishop; Anthony C. Fiumera (Molecular Ecology, 2021)
Toxicant resistance is a complex trait, affected both by genetics and the environment. Like most complex traits, it can exhibit sexual dimorphism, yet sex is often overlooked as a factor in studies of toxicant resistance. Paraquat, one such toxicant, is a commonly used herbicide and is known to produce mitochondrial oxidative stress, decrease dopaminergic neurons and dopamine (DA) levels, and decrease motor ability. While the main effects of paraquat are well‐characterized, less is known about the naturally occurring variation in paraquat susceptibility. The purpose of this study was to map the genes contributing to low‐dose paraquat susceptibility in Drosophila melanogaster , and to determine if susceptibility differs between the sexes. One hundred of the Drosophila Genetic Reference Panel (DGRP) lines were scored for susceptibility via climbing ability and used in a genome‐wide association study (GWAS). Variation in seventeen genes in females and thirty‐five genes in males associated with paraquat susceptibility. Only two candidate genes overlapped between the sexes despite a significant positive correlation between male and female susceptibilities. Many associated polymorphisms had significant interactions with sex, with most having conditionally neutral effects. Conditional neutrality between the sexes probably stems from sex‐biased expression which may result from partial resolution of sexual conflict. Candidate genes were verified with RNAi knockdowns, gene expression analyses, and DA quantification. Several of these genes are novel associations with paraquat susceptibility. This research highlights the importance of assessing both sexes when studying toxicant susceptibility.

Correction to: Infectious mononucleosis, immune genotypes, and non-Hodgkin lymphoma (NHL): an InterLymph Consortium study - Niquelle Brown Wadé; Cindy M. Chang; David Conti; Joshua Millstein; Christine Skibola; Alexandra Nieters; Sophia S. Wang; Silvia De Sanjose; Eleanor Kane; John J. Spinelli; Paige Bracci; Yawei Zhang; et al. (Cancer Causes & Control, 2020)

Infectious mononucleosis, immune genotypes, and non-Hodgkin lymphoma (NHL): an InterLymph Consortium study - Niquelle Brown Wadé; Cindy M. Chang; David Conti; Joshua Millstein; Christine Skibola; Alexandra Nieters; Sophia S. Wang; Silvia De Sanjose; Eleanor Kane; John J. Spinelli; Paige Bracci; Yawei Zhang; et al. (Cancer Causes & Control, 2020)

Circulating miRNAs expression as potential biomarkers of mild traumatic brain injury - Francesca Polito; Fausto Famà; Rosaria Oteri; Giovanni Raffa; Gianluca Vita; Alfredo Conti; Sacco Daniele; Vincenzo Macaione; Marcello Passalacqua; Salvatore Cardali; Rosa Maria Di Giorgio; Maria Gioffrè; et al. (Molecular Biology Reports, 2020)

Age-related murine hippocampal CA1 laminae oxidative stress measured in vivo by QUEnch-assiSTed (QUEST) MRI: impact of isoflurane anesthesia - Bruce A. Berkowitz; Robert H. Podolsky; Karen Lins Childers; Alexander Gow; Brandy L. Schneider; Scott C. Lloyd; Kelly E. Bosse; Alana C. Conti; Robin Roberts; Ali M. Berri; Emma Graffice; Kenan Sinan; et al. (GeroScience, 2020)
Age-related impairments in spatial learning and memory often precede non-familial neurodegenerative disease. Ex vivo studies suggest that physiologic age-related oxidative stress in hippocampus area CA1 may contribute to prodromal spatial disorientation and to morbidity. Yet, conventional blood or cerebrospinal fluid assays appear insufficient for early detection or management of oxidative stress within CA1 sub-regions in vivo. Here, we address this biomarker problem using a non-invasive MRI index of CA1 laminae oxidative stress based on reduction in R1 (= 1/T1) after anti-oxidant administration. An R1 reduction reflects quenching of continuous and excessive production of endogenous paramagnetic free radicals. Careful motion-correction image acquisition, and avoiding repeated exposure to isoflurane, facilitates detection of hippocampus CA1 laminae oxidative stress with QUEnch-assiSTed (QUEST) MRI. Intriguingly, age- and isoflurane-related oxidative stress is localized to the stratum lacunosum of the CA1 region. Our data raise the possibility of using QUEST MRI and FDA-approved anti-oxidants to remediate spatial disorientation and later neurodegeneration with age in animals and humans.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Correction to: Grotta Romanelli (Lecce, Southern Italy) Between Past and Future: New Studies and Perspectives for an Archaeo-geosite Symbol of the Palaeolithic in Europe - R. Sardella; D. A. Iurino; B. Mecozzi; D. Sigari; F. Bona; L. Bellucci; M. Coltorti; J. Conti; G. Lembo; B. Muttillo; I. Mazzini (Geoheritage, 2019)

Grotta Romanelli (Lecce, Southern Italy) Between Past and Future: New Studies and Perspectives for an Archaeo-geosite Symbol of the Palaeolithic in Europe - R. Sardella; D. A. Iurino; B. Mecozzi; D. Sigari; F. Bona; L. Bellucci; M. Coltorti; J. Conti; G. Lembo; B. Muttillo; I. Mazzini (Geoheritage, 2019)

Plant–environment interactions through a functional traits perspective: a review of Italian studies - Stefano Chelli; Michela Marignani; Elena Barni; Alessandro Petraglia; Giacomo Puglielli; Camilla Wellstein; Alicia T. R. Acosta; Rossano Bolpagni; Luca Bragazza; Giandiego Campetella; Alessandro Chiarucci; Luisa Conti; et al. (Plant Biosystems, 2019)

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Developing allometric models to predict the individual aboveground biomass of shrubs worldwide - G. Conti; L. D. Gorné; S. R. Zeballos; M. L. Lipoma; G. Gatica; E. Kowaljow; J. I. Whitworth‐Hulse; A. Cuchietti; M. Poca; S. Pestoni; P. M. Fernandes (Global Ecology and Biogeography, 2019)
Aim Existing global models to predict standing biomass are based on trees characterized by a single principal stem, well developed in height. However, their use in open woodlands and shrublands, characterized by multistemmed species with substantial crown development, generates a high level of uncertainty in biomass estimates. This limitation led us to (a) develop global models of shrub individual aboveground biomass based on simple allometric variables, (b) to compare the fit of these models with existing global biomass models, and (c) to assess whether models fit change when bioclimatic variables are considered. Location Global. Time period Present. Major taxa studied 118 species of shrubs. Methods We compile a database of 3,243 individuals across 49 sites distributed worldwide. Including stem basal diameter, height and crown diameter as predictor variables, we built potential models and compared their fit using generalized least squares. We used mixed effects models to determine if bioclimatic variables improved the accuracy of biomass models. Results Although the most important variable in terms of predictive capacity was stem basal diameter, crown diameter significantly improved the models’ fit, followed by height. Four models were finally chosen, with the best model combining all these variables in the same equation [ R 2 = 0.930, root mean square error (RMSE) = 0.476]. Selected models performed as well as established global biomass models. Including the individual bioform significantly improved the models’ fit. Main conclusions Stem basal diameter, crown diameter and height measures could be combined to provide robust aboveground biomass (AGB) estimates of individual shrub species. Our study supplements well‐established models developed for trees, allowing more accurate biomass estimation of multistemmed woody individuals. We further provide tools for a methodological standardization of individual biomass quantification in these species. We expect these results contribute to improve the quality of biomass estimates across ecosystems, but also to generate methodological consensus on field biomass assessments in shrubs.

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Porosity Estimation and Geometric Characterization of Fractured and Karstified Carbonate Rocks Using GPR Data in the Salitre Formation, Brazil - Iurianne M. M. Conti; David L. de Castro; Francisco H. R. Bezerra; Caroline L. Cazarin (Pure and Applied Geophysics, 2019)

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Reversed Auxiliary Flow to Reduce Embolism Risk During TAVI: A Computational Simulation and Experimental Study - Michele Conti; Stijn Vandenberghe; Stefania Marconi; Enrico Ferrari; Rodrigo M. Romarowski; Simone Morganti; Ferdinando Auricchio; Stefanos Demertzis (Cardiovascular Engineering and Technology, 2019)

Whale Shark Tourism: Impacts on Coral Reefs in the Philippines - C. W. Martin Wong; Inga Conti-Jerpe; Laurie J. Raymundo; Caroline Dingle; Gonzalo Araujo; Alessandro Ponzo; David M. Baker (Environmental Management, 2019)

Microparticles and autophagy: a new frontier in the understanding of atherosclerosis in rheumatoid arthritis - C. Barbati; M. Vomero; T. Colasanti; F. Ceccarelli; M. Marcosano; F. Miranda; L. Novelli; A. Pecani; Carlo Perricone; F. R. Spinelli; S. Truglia; F. Conti; et al. (Immunologic Research, 2018)

Impact of mast cells in depression disorder: inhibitory effect of IL-37 (new frontiers) - Pio Conti; Alessandro Caraffa; Gianpaolo Ronconi; Chiara M. Conti; Spiros K. Kritas; Filiberto Mastrangelo; Lucia Tettamanti; Theoharis C. Theoharides (Immunologic Research, 2018)

An updated checklist of the vascular flora alien to Italy - G. Galasso; F. Conti; L. Peruzzi; N. M. G. Ardenghi; E. Banfi; L. Celesti-Grapow; A. Albano; A. Alessandrini; G. Bacchetta; S. Ballelli; M. Bandini Mazzanti; G. Barberis; et al. (Plant Biosystems, 2018)

An updated checklist of the vascular flora native to Italy - F. Bartolucci; L. Peruzzi; G. Galasso; A. Albano; A. Alessandrini; N. M. G. Ardenghi; G. Astuti; G. Bacchetta; S. Ballelli; E. Banfi; G. Barberis; L. Bernardo; et al. (Plant Biosystems, 2018)

Filtering effect induced by rigid massless embedded foundations - Riccardo Conti; Marco Morigi; Giulia M. B. Viggiani (Bulletin of Earthquake Engineering, 2017)

Conserving plant diversity in Europe: outcomes, criticisms and perspectives of the Habitats Directive application in Italy - G. Fenu; G. Bacchetta; V. Giacanelli; D. Gargano; C. Montagnani; S. Orsenigo; D. Cogoni; G. Rossi; F. Conti; A. Santangelo; M. S. Pinna; F. Bartolucci; et al. (Biodiversity and Conservation, 2017)

The Ventotene Volcanic Ridge: a newly explored complex in the central Tyrrhenian Sea (Italy) - Marco Cuffaro; Eleonora Martorelli; Alessandro Bosman; Alessia Conti; Sabina Bigi; Filippo Muccini; Luca Cocchi; Marco Ligi; Giovanni Bortoluzzi; Davide Scrocca; Simonepietro Canese; Francesco L. Chiocci; et al. (Bulletin of Volcanology, 2016)

Fatigue of Metallic Stents: From Clinical Evidence to Computational Analysis - F. Auricchio; A. Constantinescu; M. Conti; G. Scalet (Annals of Biomedical Engineering, 2016)

Is musculoskeletal pain a consequence or a cause of occupational stress? A longitudinal study - Matteo Bonzini; Lorenza Bertu’; Giovanni Veronesi; Marco Conti; David Coggon; Marco M. Ferrario (International Archives of Occupational and Environmental Health, 2015)

Optical Characterization of Normal, Benign, and Malignant Thyroid Tissue: A Pilot Study - M. P. Brandao; R. Iwakura; F. S. Basilio; K. Haleplian; A. S. Ito; L. C. Conti de Freitas; L. Bachmann (Journal of Fluorescence, 2015)

Erratum to: Immunoreactivity and avidity of IgG anti-β2-glycoprotein I antibodies from patients with autoimmune diseases to different peptide clusters of β2-glycoprotein I - A. Artenjak; I. Locatelli; H. Brelih; D. M. Simonič; Z. Ulcova-Gallova; J. Swadzba; J. Musial; T. Iwaniec; L. Stojanovich; F. Conti; G. Valesini; T. Avčin; et al. (Immunologic Research, 2015)

Immunoreactivity and avidity of IgG anti-β2-glycoprotein I antibodies from patients with autoimmune diseases to different peptide clusters of β2-glycoprotein I - A. Artenjak; I. Locatelli; H. Brelih; D. M. Simonič; Z. Ulcova-Gallova; J. Swadzba; J. Musial; T. Iwaniec; L. Stojanovich; F. Conti; G. Valesini; T. Avčin; et al. (Immunologic Research, 2015)

Islands as model systems in ecology and evolution: prospects fifty years after MacArthur‐Wilson - Ben H. Warren; Daniel Simberloff; Robert E. Ricklefs; Robin Aguilée; Fabien L. Condamine; Dominique Gravel; Hélène Morlon; Nicolas Mouquet; James Rosindell; Juliane Casquet; Elena Conti; Josselin Cornuault; et al. (Ecology Letters, 2015)
The study of islands as model systems has played an important role in the development of evolutionary and ecological theory. The 50th anniversary of MacArthur and Wilson's (December 1963) article, ‘An equilibrium theory of insular zoogeography’, was a recent milestone for this theme. Since 1963, island systems have provided new insights into the formation of ecological communities. Here, building on such developments, we highlight prospects for research on islands to improve our understanding of the ecology and evolution of communities in general. Throughout, we emphasise how attributes of islands combine to provide unusual research opportunities, the implications of which stretch far beyond islands. Molecular tools and increasing data acquisition now permit re‐assessment of some fundamental issues that interested MacArthur and Wilson. These include the formation of ecological networks, species abundance distributions, and the contribution of evolution to community assembly. We also extend our prospects to other fields of ecology and evolution – understanding ecosystem functioning, speciation and diversification – frequently employing assets of oceanic islands in inferring the geographic area within which evolution has occurred, and potential barriers to gene flow. Although island‐based theory is continually being enriched, incorporating non‐equilibrium dynamics is identified as a major challenge for the future.

Comparative safety profiles of intravitreal bevacizumab, ranibizumab and pegaptanib: the analysis of the WHO database of adverse drug reactions - C. Biagi; V. Conti; N. Montanaro; M. Melis; E. Buccellato; M. Donati; A. Covezzoli; R. Amato; L. Pazzi; M. Venegoni; A. Vaccheri; D. Motola (European Journal of Clinical Pharmacology, 2014)

Are Red Lists really useful for plant conservation? The New Red List of the Italian Flora in the perspective of national conservation policies - G. Rossi; C. Montagnani; T. Abeli; D. Gargano; L. Peruzzi; G. Fenu; S. Magrini; M. Gennai; B. Foggi; R.P. Wagensommer; S. Ravera; A. Cogoni; et al. (Plant Biosystems, 2014)

A1R–A2AR heteromers coupled to Gs and Gi/0 proteins modulate GABA transport into astrocytes - Sofia Cristóvão-Ferreira; Gemma Navarro; Marc Brugarolas; Kamil Pérez-Capote; Sandra H. Vaz; Giorgia Fattorini; Fiorenzo Conti; Carmen Lluis; Joaquim A. Ribeiro; Peter J. McCormick; Vicent Casadó; Rafael Franco; et al. (Purinergic Signalling, 2013)

Lead Bone Toxicity in Growing Rats Exposed to Chronic Intermittent Hypoxia - María I. Conti; Clarisa Bozzini; Graciela B. Facorro; Ching M. Lee; Patricia M. Mandalunis; Lidia L. Piehl; Adriana E. Piñeiro; Antonela R. Terrizzi; María P. Martínez (Bulletin of Environmental Contamination and Toxicology, 2012)

Effects of Lead Exposure on Growth and Bone Biology in Growing Rats Exposed to Simulated High Altitude - María Inés Conti; Antonela R. Terrizzi; Ching Ming Lee; Patricia M. Mandalunis; Clarisa Bozzini; Adriana E. Piñeiro; María del Pilar Martínez (Bulletin of Environmental Contamination and Toxicology, 2012)

An integrated GIS for sedimentological and geomorphological analysis of a lagoon environment. Barra de Cananéia inlet region, (Southeastern Brazil) - Luis Américo Conti; Carlos Alberto S. Araujo; Fernando S. Paolo; Roberto L. Barcellos; Marcelo Rodrigues; Michel M. Mahiques; Valdenir V. Furtado (Journal of Coastal Conservation, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Variation in folate pathway genes and distal colorectal adenoma risk: a sigmoidoscopy-based case–control study - A. Joan Levine; Won Lee; Jane C. Figueiredo; David V. Conti; David J. Vandenberg; Brian D. Davis; Christopher K. Edlund; Susanne M. Henning; David Heber; Mariana C. Stern; Robert W. Haile (Cancer Causes & Control, 2011)

A case of primary papillary disseminated adenocarcinoma of canine lung - Maria Beatrice Conti; M. C. Marchesi; G. Angeli; E. Lepri; C. Marinetti; F. Rueca (Veterinary Research Communications, 2010)

Genes involved with folate uptake and distribution and their association with colorectal cancer risk - Jane C. Figueiredo; A. Joan Levine; Won H. Lee; David V. Conti; Jenny N. Poynter; Peter T. Campbell; David Duggan; Juan Pablo Lewinger; Maria Elena Martinez; Cornelia M. Ulrich; Polly Newcomb; John Potter; et al. (Cancer Causes & Control, 2010)

Non‐native flora of Italy: Species distribution and threats - L. Celesti‐Grapow; A. Alessandrini; P. V. Arrigoni; S. Assini; E. Banfi; E. Barni; M. Bovio; G. Brundu; M. R. Cagiotti; I. Camarda; E. Carli; F. Conti; et al. (Plant Biosystems, 2010)

Measles-induced respiratory distress, air-leak and ARDS - M. Piastra; R. Onesimo; D. Luca; L. Lancella; L. Marzano; G. Rosa; D. Pietrini; P. Valentini; G. Conti (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Olive oil adulterated with hazelnut oils: simulation to identify possible risks to allergic consumers - M. Arlorio; J.D. Coisson; M. Bordiga; F. Travaglia; C. Garino; L. Zuidmeer; R. Van Ree; M.G. Giuffrida; A. Conti; A. Martelli (Food Additives & Contaminants: Part A, 2010)

Inventory of the non‐native flora of Italy - L. Celesti‐Grapow; A. Alessandrini; P. V. Arrigoni; E. Banfi; L. Bernardo; M. Bovio; G. Brundu; M. R. Cagiotti; I. Camarda; E. Carli; F. Conti; S. Fascetti; et al. (Plant Biosystems, 2009)

Substance P Upregulates LTB4 in Rat Adherent Macrophages from Granuloma Induced by KMnO4 - M. L. Castellani; P. Conti; M. Felaco; J. Vecchiet; C. Ciampoli; G. Cerulli; P. Boscolo; T. C. Theoharides (Neurotoxicity Research, 2009)

Clinical findings and diagnosis in a case of cholangiocellular carcinoma in a horse - M. B. Conti; M. C. Marchesi; F. Zappulla; D. Buttarelli; E. Lepri; F. Passamonti; S. Galletti; G. Rucco; F. Rueca (Veterinary Research Communications, 2008)

Equine adipose-tissue derived mesenchymal stem cells and platelet concentrates: their association in vitro and in vivo - M. Del Bue; S. Riccò; R. Ramoni; V. Conti; G. Gnudi; S. Grolli (Veterinary Research Communications, 2008)

Soil N2O emissions and N2O/(N2O+N2) ratio as affected by different fertilization practices and soil moisture - E. Ciarlo; M. Conti; N. Bartoloni; G. Rubio (Biology and Fertility of Soils, 2008)

γ-Irradiation of PEGd,lPLA and PEG-PLGA Multiblock Copolymers: I. Effect of Irradiation Doses - R. Dorati; C. Colonna; M. Serra; I. Genta; T. Modena; F. Pavanetto; P. Perugini; B. Conti (AAPS PharmSciTech, 2008)

Platelet Lysate Promotes in Vitro Proliferation of Equine Mesenchymal Stem Cells and Tenocytes - M. Del Bue; S. Riccò; V. Conti; E. Merli; R. Ramoni; S. Grolli (Veterinary Research Communications, 2007)

The effect of moisture on nitrous oxide emissions from soil and the N2O/(N2O+N2) ratio under laboratory conditions - E. Ciarlo; M. Conti; N. Bartoloni; G. Rubio (Biology and Fertility of Soils, 2007)

Fungal abundance and distribution as influenced by clearing and land use in a vertic soil of Argentina - E. Gomez; R. Pioli; M. Conti (Biology and Fertility of Soils, 2006)

Generation and characterization of a mouse lymphatic endothelial cell line - Marina Sironi; Annarita Conti; Sergio Bernasconi; Anna M. Fra; Fabio Pasqualini; Manuela Nebuloni; Eleonora Lauri; Maida De Bortoli; Alberto Mantovani; Elisabetta Dejana; Annunciata Vecchi (Cell and Tissue Research, 2006)

5-Methyl-Pyrrolidinone Chitosan Films as Carriers for Buccal Administration of Proteins - C Colonna; I Genta; P Perugini; F Pavanetto; T Modena; M Valli; C Muzzarelli; B Conti (AAPS PharmSciTech, 2006)

Diet and cooling interactions on physiological responses of grazing dairy cows, milk production and composition - M. R. Gallardo; S. E. Valtorta; P. E. Leva; M. C. Gaggiotti; G. A. Conti; R. F. Gregoret (International Journal of Biometeorology, 2005)

Expression of the ?-carotene desaturase gene in sunflower - M Fambrini; M Salvini; A Conti; V Michelotti; C Pugliesi (Plant Biosystems, 2004)

Dynamics of humic fractions and microbial activity under no-tillage or reduced tillage, as compared with native pasture (Pampa Argentina) - Mirta G. Gonzlez; Marta E. Conti; R. Martha Palma; Nilda M. Arrigo (Biology and Fertility of Soils, 2003)

Oxygen supply modulates MCP-1 release in monocytes from young and aged rats: Decrease of MCP-1 transcription and translation is age-related - M. Reale; C. Di Giulio; M. Cacchio; R.C. Barbacane; A. Grilli; G. Bianchi; M. Di Gioacchino; M. Felaco; P. Conti (Molecular and Cellular Biochemistry, 2003)

Diagnosis and Treatment of Progressive Ethmoidal Haematoma (PEH) in Horses - M.B. Conti; M.C. Marchesi; F. Rueca; M. Puccetti (Veterinary Research Communications, 2003)

Inhibition of MCP-1 and MIP-2 transcription and translation by mimosine in muscle tissue infected with the parasite Trichinella spiralis - Pio Conti; Stavros Frydas; Marcella Reale; Renato C. Barbacane; M. Di Gioacchino; M. Felaco; A. Trakatellis (Molecular and Cellular Biochemistry, 2002)

Generation of TNFα, IFNγ, IL-4, IL-6 and IL-10 in Trichinella spiralis infected mice: effect of the anti-inflammatory compound mimosine - S. Frydas; N. Papaioannou; M. Hatzistilianou; D. Merlitti; M. Di Gioacchino; M.L. Castellani; P. Conti (Inflammopharmacology, 2001)

Chemical and biochemical properties as potential indicators of disturbances - N. M. Arrigo; M. E. Conti; R. M. Palma; M. I. Saubidet (Biology and Fertility of Soils, 2000)

Geochemical changes at the Bagni di Triponzo thermal spring during the Umbria-Marche 1997–1998 seismic sequence - F. Quattrocchi; R. Pik; L. Pizzino; M. Guerra; P. Scarlato; M. Angelone; M. Barbieri; A. Conti; B. Marty; E. Sacchi; G.M. Zuppi; S. Lombardi (Journal of Seismology, 2000)

Transport and consumption rate of O2 in alginate gel beads entrapping hepatocytes - M. Cristina Annesini; Giuseppe Castelli; Filippo Conti; Laura Conti De Virgiliis; Luigi Marrelli; Alfredo Miccheli; Elisabetta Satori (Biotechnology Letters, 2000)

In situ X-ray absorption spectroelectrochemical study of hydroxocobalamin - M. Giorgetti; I. Ascone; M. Berrettoni; P. Conti; S. Zamponi; R. Marassi (JBIC Journal of Biological Inorganic Chemistry, 2000)

Influence of feeding precursors on tropane alkaloid production during an abiotic stress in Datura innoxia transformed roots - M. Boitel-Conti; J-C. Laberche; A. Lanoue; C. Ducrocq; B.S. Sangwan-Norreel (Plant Cell, Tissue and Organ Culture (PCTOC), 2000)

Vitamin B6-deficient diet plus 4-deoxypyridoxine (4-DPD) reduces the inflammatory response induced by T. spiralis in diaphragm, masseter and heart muscle tissue of mice - S. Frydas; N. Papaioanou; I. Vlemmas; I. Theodoridis; G. Anogiannakis; D. Vacalis; A. Trakatellis; R.C. Barbacane; M. Reale; P. Conti (Molecular and Cellular Biochemistry, 1999)

IgG, IgG1 and IgM response in Trichinella spiralis-infected mice treated with 4-deoxypirydoxine or fed a Vitamin B6-deficient diet - S. Frydas; M. Reale; D. Vacalis; R.C. Barbacane; F.C. Placido; I. Cataldo; M. Di Gioacchino; E. Karagouni; E. Dotsika; G. Anogiannakis; A. Trakatellis; P. Conti (Molecular and Cellular Biochemistry, 1999)

Expression of lymphocyte subpopulations, cytokine serum levels, and blood and urinary trace elements in asymptomatic atopic men exposed to an urban environment - P. Boscolo; M. Di Gioacchino; E. Sabbioni; F. Benvenuti; P. Conti; M. Reale; P. Bavazzano; G. Giuliano (International Archives of Occupational and Environmental Health, 1999)

RFLP mapping of quantitative trait loci controlling abscisic acid concentration in leaves of drought-stressed maize (Zea mays L.) - R. Tuberosa; M. C. Sanguineti; P. Landi; S. Salvi; E. Casarini; S. Conti (Theoretical and Applied Genetics, 1998)

Induction of monocyte chemotactic protein-1 (MCP-1) and TNF alpha by Trichinella spiralis in serum of mice in vivo - M. Reale; S. Frydas; R.C. Barbacane; F.C. Placido; I. Cataldo; P. Conti; D. Vacalis; A. Trakatellis; G. Anogianakis; M. Felaco; M. Di Giocchino (Molecular and Cellular Biochemistry, 1998)

Influence of tillage system on denitrification in maize-cropped soils - R. M. Palma; M. Rímolo; M. I. Saubidet; M. E. Conti (Biology and Fertility of Soils, 1997)

Relationship of soil carbon light fraction, microbial activity, humic acid production and nitrogen fertilization in the decaying process of corn stubble - M. E. Conti; N. M. Arrigo; H. J. Marelli (Biology and Fertility of Soils, 1997)

Protective effects of melatonin in mice infected with encephalitis viruses - D. Ben-Nathan; G. J. M. Maestroni; S. Lustig; A. Conti (Archives of Virology, 1995)

Characterization of rat brain cellular membrane components acting as receptors for vesicular stomatitis virus - C. Conti; P. Mastromarino; M. G. Ciuffarella; N. Orsi (Archives of Virology, 1988)

Inhibition of rabies virus infection by a soluble membrane fraction from the rat central nervous system - C. Conti; B. Hauttecoeur; M. J. Morelec; B. Bizzini; N. Orsi; H. Tsiang (Archives of Virology, 1988)

Deoxyribonucleic acid base compositions of hyphomicrobia - M. Mandel; P. Hirsch; S. F. Conti (Archives of Microbiology, 1972)